A CONCEPTUAL MODEL FOR COMPREHENSIVE ASSURANCE REVIEW ENGAGEMENTS FOR LESS DEVELOPED REGULATORY ENVIRONMENTS. Issue 1 (2nd January 2023) - Anomah, Sampson; Ayeboafo, Boadu; Aguabeng, Owusu
Abstract: Assurance review practitioners are demanded not only to provide information to enhance the credibility of a subject matter or evaluate whether the subject matter conforms with suitable criteria but they are also demanded to be the decision makers' consultants on the subject matter. For this reason, a strong alignment of assurance review processes with management processes has become imperative to reduce their exposure to failure. The existing models used for assurance reviews do not provide sufficient guidance in jurisdictions with less developed regulatory environments. The study designed a conceptual model to guide assurance review practices. An action design research approach involving interactions at various stages with stakeholders was employed to design and collect data for the evaluation of a proposed intervention. Factor analysis and regression analysis were applied to the data collected and the results confirmed all six principal components and twenty out of twenty-one principles that constitute the proposed model. A composite reliability assessment of the model provided values greater than 0.7 which was adequate proof of its internal consistency. Similarly, the convergent reliability of the model showed that all the variables were above the threshold value of 0.5. These indicated that the model is valid, and reliable and supports the generalized use by assurance reviewers committees to improve performance. The study contributes to the practice of assurance reviews because it built an artifact to guide generic and customized assurance review engagements.